PERBANDINGAN ANTARA PUISI “SAJAK JATUH CINTA” KARYA EMHA AINUN NADJIB DAN PUISI “SAJAK KECIL TENTANG CINTA” KARYA SAPARDI DJOKO DAMONO - Yusrina Ayu Linati; Yosi Wulandari (RUANG KATA: Journal of Language and Literature Studies, 2022)
Emha Ainun Nadjib's poem "The Sajak of Falling in Love" and Sapardi Djoko Damono's "Small Poem About Love" have many similarities and contrasts, which the authors of this study try to describe. Focus will be placed on comparing the poetic structure of the two works as part of a comparative literary study. This study uses a comparative research technique. Reading, listening, taking notes, and copying were used to obtain the data in this study. After all the data is collected, the data reduction process begins. It's time to examine the data we've collected and categorize it to make a final decision about what research we're going to do next. The hypogram is found in Emha Ainun Nadjib's poem "The Poem of Falling in Love", while the transformation is found in Sapardi Djoko Damono's poem "Little Poetry About Love". The two poems have the same meaning, each of which tells about true love for the Almighty or true love for the Almighty in general. There are several similarities and differences between the two literary works, which lie in the theme, taste, tone, word and image. In addition to the similarities, there are also differences in them, namely mandate, rhyme, typography, and concrete words. Poems that have been converted into Hipograms, such as the Sajak Falling in Love by Emha Ainun Nadjib, can be compared to see how the weight of emotions can be measured and balanced with other aspects of life. This is why data analysis is currently being carried out. Sapardi Djoko Damono's Little Poem About Love, which emphasizes that one must learn to love oneself first before loving others, became the catalyst for this change.Keyword: Poetry, Comparison, Story